The inositol 1,4,5-trisphosphate receptor is essential for T-cell receptor signaling. - Jayaraman, T (1995)
Antigen-specific activation of T lymphocytes, via stimulation of the T-cell antigen receptor (TCR) complex, is marked by a rapid and sustained increase in the concentration of cytoplasmic free Ca2+ ([Ca2+]i). It has been suggested that the second messenger inositol 1,4,5-trisphosphate (IP3) produced after TCR stimulation binds to the IP3 receptor (IP3R), an intracellular Ca(2+)-release channel, and triggers the increase in [Ca2+]i that activates transcription of the gene for T-cell growth factor interleukin 2 (IL-2). However, the role of the IP3R in T-cell signaling and possibly in plasma membrane Ca2+ influx in T cells remains unproven. Stable transfection of T cells (Jurkat) with antisense type 1 IP3R cDNA prevented type 1 IP3R expression, providing a tool for dissecting the role of IP3 signaling during T-cell activation. T cells lacking type 1 IP3R failed to increase [Ca2+]i or produce IL-2 after TCR stimulation. Moreover, depletion of intracellular Ca2+ stores without TCR activation stimulated Ca2+ influx in cells lacking the type 1 IP3R. These results establish that the type 1 IP3R is required for intracellular Ca2+ release that triggers antigen-specific T-cell proliferation but not for plasma membrane Ca2+ influx.